Intellectual sacrifice and other mimetic paradoxes - Bubbio, Paolo Diego (Studies in Violence, Mimesis, and Culture Ser, 2018)
Contents -- Preface -- Acknowledgments -- Abbreviations -- Part 1. Intellectual Sacrifice -- Chapter 1. Intellectual Expulsion -- Chapter 2. Historical Forms of Mystification -- Chapter 3. The Path of Demystification -- Conclusion -- A Letter from RenÃ© Girard -- Part 2. Other Mimetic Paradoxes -- Transition: Corrections and Paradoxes -- Girardâs Ontological Argument for the Existence of God -- Mimetic Theoryâs Post-Kantian Legacy -- Mimetic Theory and Hermeneutic Communism -- The Self in Crisis -- Hermeneutic Mimetic Theory -- Bibliography